2016
DOI: 10.1007/s11356-016-6389-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the removal of some pharmaceutical compounds in hospital wastewater treatment plants operating in Saudi Arabia

Abstract: The concentrations of 12 pharmaceutical compounds (atenolol, erythromycin, cyclophosphamide, paracetamol, bezafibrate, carbamazepine, ciprofloxacin, caffeine, clarithromycin, lidocaine, sulfamethoxazole and N-acetylsulfamethoxazol (NACS)) were investigated in the influents and effluents of two hospital wastewater treatment plants (HWWTPs) in Saudi Arabia. The majority of the target analytes were detected in the influent samples apart from bezafibrate, cyclophosphamide, and erythromycin. Caffeine and paracetamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(44 citation statements)
references
References 75 publications
(106 reference statements)
3
39
1
1
Order By: Relevance
“…These results revealed that there is no significant difference in ATE concentration between these two WWTPs (p>0.05). Compared to the levels observed in the present study, lower concentrations of ATE have been reported in hospital WWTP effluents (0.055 μ g/L) in Saudi Arabia [ 68 ]. The high concentrations of ATE in WWTP-A effluent may be related to its high usage by the hospital.…”
Section: Discussioncontrasting
confidence: 87%
“…These results revealed that there is no significant difference in ATE concentration between these two WWTPs (p>0.05). Compared to the levels observed in the present study, lower concentrations of ATE have been reported in hospital WWTP effluents (0.055 μ g/L) in Saudi Arabia [ 68 ]. The high concentrations of ATE in WWTP-A effluent may be related to its high usage by the hospital.…”
Section: Discussioncontrasting
confidence: 87%
“…In wastewater, although decomposed products such as ammonium, nitrite, and nitrate play a pivotal role in the water ecosystem, and nitrogen content is essential to oxidation capacity of the activated sludge, excessive amounts of such substances may form carcinogens. In the study of Al Qarni et al, and Liu, it is reported that the maximum removal of NH 4 + and NH 3 reached 99% and 95% for aerobic and MBR processes, respectively [6,30]. This is comparable with the results of this study, where nitrification and nitrate reduction achieved more than 80%, corresponding to 4.9 g/L of average total nitrogen in the effluent.…”
Section: Concentrations Of Nitrogen Compoundssupporting
confidence: 89%
“…Antibiotics were detected in appreciable amounts at the inlet of the wastewater treatment plant. Example includes: a high concentration of sulfamethoxazole (59.28 μg L -1 ) was detected at the influent of the WWTP, Northern water works, Durban, South Africa [10]; among the 12 pharmaceutical compounds investigated by Qarni and co-workers (2016), sulfamethoxazole was found in the influents and effluents of two hospital WWTPs in Saudi Arabia [11]; of the 22 representative antibiotics studied by Zhang et al (2016), sulfadiazine (396 ng L -1 ) and sulfamethazine (382 ng L -1 ) were the dominating antibiotics in the influent, and the concentrations of selected antibiotics ranged from ND-41.8 ng L -1 in the effluent-receiving river [12]; and in a nationwide groundwater survey conducted by the United States Geological Survey (USGS), sulfamethoxazole appeared in 23% of the samples at an average concentration of 1.11 µg L -1 .…”
Section: Antibiotics Analysismentioning
confidence: 99%